Austinixa bragantina Coelho, 2005: a junior synonym of A. aidae (Righi, 1967) (Brachyura: Pinnotheridae) supported by integrative morphological and molecular data - Almeida, Alexandre O.; Araújo-Silva, Catarina L.; Lucatelli, Debora; Bezerra, Luis Ernesto A.; Balbino, Felipe C.; Tamburus, Ana F.; Mantelatto, Fernando L. (Zootaxa, 2023)
Austinixa bragantina Coelho, 2005, described from Ilha Canela, Bragança, state of Pará, Brazil, is established as a junior synonym of A. aidae (Righi, 1967) based on morphological (gross morphology and scanning electron microscopy) and molecular (16S rRNA mitochondrial marker) evidence. The phylogenetic tree was obtained through the Maximum Likelihood method aiming to contextualize A. bragantina among related species. We provide a redescription, an updated synonymy, and remarks on the intra-specific morphological variability of A. aidae to clarify some taxonomic inconsistencies previously reported. Austinixa hardyi Heard & Manning, 1997, a species of uncertain taxonomic status, was confirmed genetically to also be a synonym of A. aidae.